Development of a National Occupational Safety and Health Programme in Ukraine: gender aspect - Лагутіна Ірина Вікторівна; Лагутина Ирина Викторовна; Lagutina Irina V. (My University, 2012)
The article emphasizes that decent work is recognized as the first step towards greater social integration and to create conditions for comprehensive development of the individual, realization of personal non-property labour rights. Of particular importance is the provision of safe work as components of the concept of "decent work".

У статті підкреслюється, що гідна праця визнається першим кроком на шляху до більшої соціальної інтеграції, створення умов для всебічного розвитку особистості, реалізації особистих немайнових трудових прав. Особливе значення набуває забезпечення безпечної праці як складові поняття "гідна праця".

В статье подчеркивается, что достойный труд признается первым шагом на пути к большей социальной интеграции, созданию условий для всестороннего развития личности, реализации личных неимущественных трудовых прав. Особое значение приобретает обеспечение безопасного труда как составляющих понятия "достойный труд".
Lagutina I. V. Development of a National Occupational Safety and Health Programme in Ukraine: gender aspect / I. V. Lagutina // Юридичний вісник. – 2012. – № 1. – С. 62-67.
Keywords: decent work; safe working conditions; gender difference; occupational accidents; occupational diseases; development policy; regional development; гідна праця; безпечні умови праці; нещасні випадки; професійні захворювання; достойный труд; безопасные условия труда; несчастные случаи; профессиональные заболевания